Receiving and The Capacitive Profile of The Capacitors Arrangements on The Base of Natural Rubber with The Addition of MnCl2 or SnCl2 and The Active Carbon - Borowski, Tomasz (Asian Journal of Chemistry, 2010)
A method to receive cheap capacitor materials with variable demanddependent capacitance values is presented in an easy way. Examination of capacitive properties was done at 20 °C. Mean capacitance range was between 4.7 and 28.8 F/g. The capacitive systems were examined on circuits with decade resistors and capacitors.